Revitalization of Community Parks Based on the Concept of Islamic Gardens : Case Study: Riverbank of the Deli River on Ileng Street, Rengas Pulau, Medan Marelan District - Rizka Amanda; Abdiyanto Abdiyanto; Ruri Prihatini Lubis; Rahmadhani Fitri (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Green Open Space (RTH) is an essential element in urban development, playing a crucial role in supporting ecological balance, providing shade, producing oxygen, and absorbing pollution. It also serves as a social and cultural space for the community. The neighborhood park located along the banks of the Deli River on Ileng Street, Medan Marelan District, represents a concrete example of this issue. The current condition of Ileng Park reflects a decline in its quality as a green open space. This study aims to identify existing problems in terms of the park's physical condition, functionality, and user activities. It employs a qualitative descriptive approach grounded in a case study framework, with data collected from both primary and secondary sources. The analysis is conducted using a rationalistic site analysis method. The findings indicate that the community perceives a need for the revitalization of the park to enhance comfort, attractiveness, and the implementation of the Islamic Garden Concept, which is considered appropriate for restoring the park’s function as a green open space.